Exploring the Dynamics of Relational Responding Using Visual and Auditory Stimuli: Replicating Two Prominent IRAP Effects. - Parreiras, Germanna Costa; Chimura, Willian da Costa; Harte, Colin; Barnes-Holmes, Dermot; Bortoloti, Renato (Psychological Record, 2025)
The implicit relational assessment procedure (IRAP) traditionally uses visual stimuli to assess responding to verbal relations. The current study developed a modified IRAP to include the presentation of auditory stimuli. The research aimed to analyze the impact of the use of auditory stimuli (relative to visual stimuli only) on the emergence of two effects commonly observed in the IRAP literature: the single trial-type dominance effect (STTDE) and dissonant target trial-type effect (DTTTE). In addition, with respect to auditory stimuli, the impact of neutral versus emotionally intonated stimuli was also explored. Ninety participants were randomly assigned to complete one of three IRAPs: one which employed visual stimuli only, one which employed both visual and neutral auditory stimuli, and one which employed visual and positively/negatively valenced auditory stimuli. Results indicated that the STTDE and DTTTE were replicated within all three IRAPs, independent of stimulus modality. It is notable that no statistically significant differences emerged between trial-type effects across the three IRAPs, suggesting that the media of contact employed did not differentially affect participant responding. These findings provide support for the generality of the IRAP as a context for studying AARR independent of stimulus modality. This and other issues are discussed.